Insomnia and daytime sleepiness are risk factors for depressive symptoms in the elderly - Jaussent, Isabelle; Bouyer, Jean; Ancelin, Marie-Laure; Akbaraly, Tasnime; Pérès, Karine; Ritchie, Karen; Besset, Alain; Dauvilliers, Yves (Sleep (New York, N.Y.), 2011)
Previous studies have reported that insomnia and excessive daytime sleepiness (EDS) may predict depression in adults. However, these associations have not been investigated in community-dwelling elderly taking into account insomnia symptoms, EDS, and sleep medication. Four-year longitudinal study. The French Three-City Study. 3824 subjects aged ≥ 65 years and free of depressive symptoms at baseline. Questionnaires were used to evaluate "insomnia symptoms", EDS, and sleep medication at baseline. Depressive symptoms (DEP-s) were assessed using the Center for Epidemiologic Studies-Depression scale at baseline, and at 2-year and 4-year follow-up. Logistic regression models controlling for potential confounders were generated to determine whether sleep disturbances were associated with incident DEP-s and to determine the effect of individual insomnia symptoms. Insomnia symptoms and EDS independently increased the risk of incident DEP-s (OR=1.23, 95% CI=1.01-1.49 and OR=2.05, 95% CI=1.30-3.23, respectively). Poor sleep quality and difficulty in initiating and in maintaining sleep-but not early morning awakening-were identified as risk factors of DEP-s, with risk increasing with the frequency of insomnia symptoms. Sleep medication was not only a risk factor for DEP-s independent of insomnia symptoms (OR=1.62, 95% CI=1.26-2.09), but also independent of EDS (OR=1.71 95%=1.33-2.20). Insomnia symptoms, EDS, and the use of medication independently increase the risk of subsequent depression in the elderly. In clinical practice, disturbed sleep and prolonged use of sleep medication may be early indicators or potentially reversible risk factors for depression, suggesting the need for further clinical interventional research.